Leveraging online news for language learning across diverse educational contexts - İbrahim Halil Topal (Literacy Trek, 2023)
Digitization has made the news accessible to many people worldwide. Since it contains large quantities of authentic language input, online news has riveted language learners, teachers, and educators. Despite the availability of multitudes of studies on online news, research is needed to explore its potential benefits and drawbacks to guide language education. To that end, this exploratory research presented the possible educational impacts of online news on language education, offered a practical guideline for language teachers, and suggested specific news websites to utilize. The examination of a systematic literature review revealed eight potential advantages (real-world context, vocabulary expansion, grammatical/syntactical practice, heightened cultural awareness, practice/improvement in four skills, authentic language input, and content diversity) and disadvantages (linguistic complexity, content bias and inaccuracy, limited interactivity, time consumption, accessibility, and technology dependency, information overload, digital distraction, and privacy concern). Accordingly, a five-step practical guideline for using online news for classroom teaching is suggested for language teachers. The research offers news websites beneficial to multilingual and multicultural learning and awareness. Finally, the research concludes with some limitations and recommendations for future studies.